Implementation of Playing Approach in an Effort to Improve Basic Passing Skills in Basketball Games - Afif, Ridwan; Wiyanto, Agus; Astuti, Anjar Tri (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. Physical education is an educational process that is designed to enhance the overall development of individuals by fostering their physical, mental, and social well-being. Physical education encompasses a diverse array of physical activities, including running, leaping, and exercising, that contribute to the enhancement of an individual's overall physical fitness. The objective of this investigation is to evaluate the enhancement of learning outcomes associated with particular chest pass movements in basketball games by employing a play-based methodology. The learning outcomes of chest transfers in basketball games will be examined in this study in relation to the play approach. Materials and Methods. This investigation implements the classroom action research (CAR) methodology, employing class XF of SMA Negeri 6 Semarang, which comprises 21 female students and 15 male students. Data was gathered through the use of data collection instruments, such as observation sheets and tests, during the observation and measurement stages. Results. The study's findings indicated that the play approach method can enhance the chest pass skills of students. Prior to employing the play approach, the average value indicated that 39% of students had completed the course, while 61% had not. The percentage of students who completed cycle I increased to 67% after the play approach was implemented, while the percentage of students who did not complete cycle I was 33%. The percentage of improved chest pass learning outcomes in basketball games was achieved through the play approach during the second cycle stage, which made use of the same treatment. Conclusion. The results of the treatment cycles I and II indicated that the learning outcomes for chest passes in basketball games were improved through a playing approach.